Фольклоризм української літератури як дескриптивний код - Кривенко, О.В. (Культура народов Причерноморья, 2014)
У статті розглянуто, систематизовано та проілюстровано прояви фольклоризму в
українській літературі як дескриптивний код, що дає можливість довести походження родо-жанрової
та художньо-виражальної систем із синкретичних магічних текстів. Марковано передвісники
формування цих систем. Встановлено основні прийоми, за допомогою яких здійснювався перенос
уснопоетичних елементів до художньої літератури. За посередництвом літературних творів
відновлено контекст побутування деяких типів українських фольклорно магічних текстів. В статье рассмотрены, систематизированы и проиллюстрированы проявления
фольклоризма в украинской литературе как дескриптивный код, дающий возможность доказать
происхождение родо-жанровой и художественно-выразительной систем из синктеричных магических
текстов. Маркированы предпосылки формирования этих систем. Установлены основные приёмы,
посредством которых осуществлялся перенос устнопоэтических элементов в художественную
литературу. Через литературные произведения восстановлен контекст бытования некоторых типов
украинских фольклорномагических текстов. The article is devoted to the manifestations of a folklorizm in the Ukrainian literature, which are
considered as the descriptive code. These cases of form and content stylization are considered, systematized and
illustrated. As the main material for research the Ukrainian literature of the period of an early modernism
served. It is reported that a set of types of magic texts are to some extent interpreted in literature.
According to the article the analyzed literary works gave the chance to restore the context of some Ukrainian
incantations.
The article touches upon the issue of research of incantations as first of all the art texts which laid the
foundation of poetics of folklore and literature. The article gives a detailed analysis of such folklore genres as
oaths, bozhba, damnations, wishes, toasts, congratulations, various etiquette formulas, which can be met in the
Ukrainian literature of the end of the 19th beginning of the 20th century.
Much attention is given to prove an origin of almost all genres and means of expression from the syncretism of
magic texts. The prerequisites of formation of these two systems of literary systematization are marked. The main
means, which are using to transfer the folklore elements in literature, was established. It is spoken in detail
about the personification, symbol, metaphor, paralellizm, constant epithets, which were rather productive
models of magic thinking. The fact that the spells are the most archaic genre is stressed.